Mechanical, Thermal, and Morphological Analysis of 3D-Printed Polylactic Acid–Polyester Urethane Blends with Varied Infill and Material Compositions - Raju, Suchetha N.; Raju, Suchetha N.; Devi, S.H. Kameshwari; Ajeya, K.P.; Prashantha, K. (Journal of Research Updates in Polymer Science, 2025)
Multimaterial 3D printing allows for the production of intricate parts with customized mechanical properties, enhancing the versatility of material extrusion additive manufacturing. Typically, 3D printing machines are fed with commercially available filament feedstock, which limits the 3D printing of multiple materials. Hence, this study introduces in-house prepared filaments for creating polymer blend structures with improved properties. In this study, polylactic acid and thermoplastic poly ester urethane (PEU) blends with different composition ratios were processed by varying the infill densities to evaluate their impacts on their thermal, mechanical and morphological properties. The effects of infill percentage on the mechanical, thermal and morphological behaviour were investigated. The results indicate that increasing the infill percentage tends to significantly increase the elastic modulus and tensile strength. The maximum strain increased as the infill percentage increased. Overall, the mechanical results indicated that, without sacrificing any tensile strength, the composite with 25% PEU exhibited better toughness than did the neat PLA and could be printed similarly to that of PLA. Furthermore, scanning electron images revealed that the blends had a homogeneous structure with a fibrillar morphology. These results indicate that 3D printing is an effective technique for creating next generation 4D materials.